2020
DOI: 10.3390/su12020478
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Drivers of the Surface Urban Heat Island in 36 Major Cities in China: A Comparison of Two Different Methods for Delineating Rural Areas

Abstract: Urban heat islands (UHIs) are an important issue in urban sustainability, and the standardized calculation of surface urban heat island (SUHI) intensity has been a common concern of researchers in the past. In this study, we used the administrative borders (AB) method and an optimized simplified urban-extent (OSUE) algorithm to calculate the surface urban heat island intensity from 2001 to 2017 for 36 major cities in mainland China by using Moderate Resolution Imaging Spectroradiometer (MODIS) images. The spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…Although the thermal environment in pedestrian space is primarily controlled by the amount of solar radiation, vegetation, paving materials etc., the methods for selecting appropriate evaluation indicators for studying the spatial distribution of thermal comfort remain largely unclear. Few previous studies have focused on the differences in spatial distribution, with most of the comparison generally focused on the spatiotemporal distribution [55]. However, the most important purpose to study thermal comfort in pedestrian spaces is to explore the factors that cause differences in spatial distribution and to propose suggestions for further mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the thermal environment in pedestrian space is primarily controlled by the amount of solar radiation, vegetation, paving materials etc., the methods for selecting appropriate evaluation indicators for studying the spatial distribution of thermal comfort remain largely unclear. Few previous studies have focused on the differences in spatial distribution, with most of the comparison generally focused on the spatiotemporal distribution [55]. However, the most important purpose to study thermal comfort in pedestrian spaces is to explore the factors that cause differences in spatial distribution and to propose suggestions for further mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the definition of SUHII was not uniform in the literature, which resulted in different SUHII across different papers, even though the same study area was used. The discussion of SUHII defined by two different rural areas also confirmed that a large difference existed between different SUHII definitions [37].…”
Section: Introductionmentioning
confidence: 60%
“…A large amount of uncertainty in selecting rural references in the SUHI intensity calculations makes it challenging to compare the conclusions of related literature [38,64]. In contrast, taking administrative boundaries (AB) as a rural reference is considered an appropriate SUHI standardized calculation scheme and has been widely used in SUHI studies around the world, including China and the United States [19,65].…”
Section: Suhi Intensity Calculationmentioning
confidence: 99%
“…Previous empirical research models for SUHI driver analysis can generally be divided into two main categories. The first type includes global-scale analysis methods, such as correlation coefficients [28,35,36], ordinary least square (OLS) [37][38][39], generalized additive model (GAM) [40], and various models for machine learning [41][42][43]. The biggest problem with these methods is that they cannot adequately analyze the spatial variations of SUHI drivers, making them feasible for small regional studies but leading to obvious bias at large spatial scales, such as in China.…”
Section: Introductionmentioning
confidence: 99%